Indigenous Srimpi Pandelori As Android-Based Civic E-Learning Media Toward Students’ Creative Thinking Skills Engagement - Serlina Candra Wardina Sari; Mukhamad Murdiono; Kharisma Fenditasari; Isna Sari Rukmana (Jurnal Pendidikan Indonesia, 2019)
Learning media development have been a current issue in civic education. Involving to analyze indigenous Srimpi Pandelori dance based-android civic e-learning media effect aims to facilitate 4.0 era demand. Indeed, practicing 21st century skills focused on creative thinking skills. Research methodology uses a quantitative approach, a quasi-experimental study is used regarding to one group pretest posttest design. Creative thinking skills test conduct for pretest and posttest question consisting of ten multiple choice questions according to high order thinking skills criteria then checked for the Content Validity Index. To conclude, indigenous Srimpi Pandelori dance based-android media civic e-learning significantly influence students’ creative thinking skills on Pancasila values. In addition, it is able to improve students’ creative thinking skills on Pancasila values of 0.48 in medium category.